Mitochondrial dysfunction and apoptotic signaling induced by the combined action of 2-aminoethyl dihydrogen phosphate and methyl-β-cyclodextrin in melanoma cells - Duarte de Oliveira, Thalles Anthony; Nascimento Ribeiro, Ranya Sthephanie; Nogueira Laiso, Rosa Andrea; Alves, Monique Gonçalves; Moreira Sousa, Yasmim Emilly; Teles Pacheco de Matos, Ícaro Gabriel; da Conceição Rabelo, Daniel; Grassi Rici, Rose Eli; Chammas, Sergio Mestieri; Afeche, Solange Castro; Doná Rodrigues Almeida, Gustavo Henrique; Maria, Durvanei Augusto (Frontiers in Pharmacology, 2026)
Melanoma cells exhibit remarkable metabolic adaptability, sustained by lipid enrichment and mitochondrial resilience that enable survival under stress. Disrupting these bioenergetic and structural supports may represent an effective therapeutic avenue. This study investigated the antiproliferative, pro-apoptotic, and mitochondrial effects of 2-aminoethyl dihydrogen phosphate (2-AEH2P), alone and in combination with methyl-β-cyclodextrin (MβCD) in human (SK-MEL-28) and murine (B16-F10) melanoma cells, compared with normal human (FN1) and murine (L929) fibroblasts. Cell viability, proliferation index, mitochondrial membrane potential (ΔΨm), cell-cycle distribution, and apoptotic marker expression were evaluated following single and combined treatments. Morphological alterations were examined microscopically, and pharmacodynamic interaction was analyzed through drug-synergy assessment. 2-AEH2P displayed selective cytotoxicity toward melanoma cells, with markedly lower IC50 values than fibroblasts. Its combination with MβCD potentiated these effects, producing strong additive cytotoxicity. Treated melanoma cells showed distinct morphological alterations, including cytoplasmic projections and abnormal division, while fibroblasts preserved normal morphology. Combined treatments disrupted the cell-cycle profile, reducing G0/G1 and increasing S and G2/M phases, and induced mitochondrial dysfunction, evidenced by a significant decrease in ΔΨm. Expression of apoptotic markers (caspases-3 and -8, cytochrome c, p53, and Bad) increased, whereas anti-apoptotic Bcl-2 was downregulated. The combined use of 2-AEH2P and MβCD induced selective cytotoxicity in melanoma cells by disturbing lipid–mitochondrial homeostasis and activating intrinsic apoptotic signaling. These findings support a dual-target metabolic–membrane approach that exploits metabolic and mitochondrial vulnerabilities of melanoma and warrant further studies to elucidate its mechanisms and translational potential.